2020
DOI: 10.1002/cptc.202000146
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizable Oxime Esters: An Efficient Photoinitiator with Low Migration Ability for 3D Printing to Fabricate Luminescent Devices

Abstract: The development of novel visible light photoinitiators (PIs) with low mobility for 3D printing will open up new applications for photopolymerization. In this work, a polymerizable visible light PI DCCA containing an oxime acryloyl ester structure was designed and synthesized. Its linear absorption has a maximum in the visible region (400-480 nm), overlapping well with the emission spectra of conventional blue light sources, and it can effectively induce acrylate polymerization under irradiation with a 450 nm L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…After stirring for another 30 min, the mixture was filtered, washed with water, pentane, and dried under vacuum (2.02 g, 86% yield). 1 H NMR (400 MHz, DMSO-d 6 ) δ 8.81 (d, J = 2.8 Hz, 1H), 8.51–8.33 (m, 2H), 7.59 (d, J = 9.1 Hz, 1H) Analyses were consistent with those previously reported in the literature [ 24 ].…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…After stirring for another 30 min, the mixture was filtered, washed with water, pentane, and dried under vacuum (2.02 g, 86% yield). 1 H NMR (400 MHz, DMSO-d 6 ) δ 8.81 (d, J = 2.8 Hz, 1H), 8.51–8.33 (m, 2H), 7.59 (d, J = 9.1 Hz, 1H) Analyses were consistent with those previously reported in the literature [ 24 ].…”
Section: Methodssupporting
confidence: 88%
“…Moreover, the Iod/NPG (1%/1% w / w ) couple weakly initiates the FRP (FC = 47%). This is ascribed to the formation of a charge transfer complex (CTC) between Iod and NPG [ 24 ] which is able to generate reactive species when it absorbs light. Clearly, the presence of Coumarin as photoinitiator is improving the performance of the photopolymerization processes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on other elegant studies that have specifically reported coumarin-based oxime-esters as highly efficient visible light photoinitiators, containing phenyl [18,19,20] and methoxy groups [18] as substituents, in the present paper, we studied the coumarin-based oxime-ester structural effect 3 on the associated photoreactivity by introducing new substituents. More particularly the huge role of the decarboxylation reaction affected by the ester group is highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…The use of light-emitting diodes (LEDs) for photopolymerization applications have recently generated increased attention because of their efficient light output and low cost. [18][19][20] However, the development of new and efficient LEDsensitive PIs and PISs, such as oxime esters, [21][22][23][24][25] D-π-Acontaining photoacid generators, 16,18,26,27 and host-guest dye PIs, including ion-pair complexes, [28][29][30] is challenging.…”
Section: Introductionmentioning
confidence: 99%